Observables and Symmetries of n-Plectic Manifolds - Ryvkin, Leonid (BestMasters, 2016)
Leonid Ryvkin gives a motivated and self-sustained introduction to n-plectic geometry with a special focus on symmetries. The relevant algebraic structures from scratch are developed. The author generalizes known symplectic notions, notably observables and symmetries, to the n-plectic case, culminating in solving the existence question for co-moment maps for general pre-n-plectic manifolds. Finally partial results scattered along the literature are derived from our general result. Contents Strongly Homotopy Lie Algebras Observables and Symmetries of n-Plectic Manifolds Target Groups Researchers and students in the fields of algebra and geometry Pracitioners in these areas The Author Leonid Ryvkin wrote his master thesis at the Ruhr-Universität Bochum and is currently working on his PhD studies.